Modernisation of the Strategic Planning for Decarbonisation in Kazakhstan - Yessekina, Bakhyt; Shalabekova, Aliya; Koshumov, Askhat; Junusbekova, Gulsara (International Journal of Energy Economics and Policy, 2021)
This study examines the issues of modernisation of the state planning system in the Republic of Kazakhstan, taking into account the Paris Climte Agreement and new pledge on achievement of the carbon neutrality. Based on the generalisation of the international experience of the OECD countries, authors determine the main approaches, principles and priorities for adapting the strategic planning system to the conditions of climate change and global risks. According to the authors opinion, approaches to imporovement of the planning system in terms of decarbonisation should be based on the OECD methodology. In conclusion, the authors substantiates the recommendations to the Government of Kazakhstan on improvement of the state planning system trough an integration of the SEA and decarbonisation principles. Keywords: climate change adaptation, state planning system, decarbonisation of economy, emission of the GHGs, energy efficiency, renewables, monitoring approaches. JEL Classifications: Q5,Q54, Q56, O3 DOI: https://doi.org/10.32479/ijeep.11308